Gender-variability of minimum foot clearance during walking in adults and elderly - Sousa, Tiago Emanuel Loureiro de (2018)
Falls are a public health problem faced by many countries representing a heavy burden for societies, particularly for those in which the population is aging. In fact, a high risk of falls is associated with older age groups. The increased frequency of falls in the elderly is responsible for many deaths and unintentional accidents impacting negatively their quality of life. It has been suggested that women are at a higher risk of falling than men, although little is known whether the factors that affect the risk of falls vary between men and women. The minimum foot clearance and its variability is an important parameter of gait which can be related to the mechanism of falls. The present study aims to investigate older adults’ gender-related differences in minimum foot clearance, particularly its variability/complexity during walking. This study included 43 physically active subjects, of whom 23 were women and 20 were men. Participants walked on a treadmill for 14 minutes at a preferred walking speed. Minimum foot clearance data were obtained through a 3D motion capture system using 8 infrared cameras at a sampling frequency of 100 Hz. Sixteen retroreflective markers of 10 mm were placed on the anatomical landmarks of the right and left sides according to the recommendations of the Plug-in-Gait Lower Body model. Three additionally half markers of 10 mm were placed into each shoe for proper determination of minimum foot clearance, during gait. The results showed that women had a lower mean in the minimum foot clearance (11.63 mm) compared to men (14.84 mm). Regarding the complexity of the minimum foot clearance, no gender differences were found. In conclusion, although men and women had similar complexity of minimum foot clearance, the women exhibited a minimum foot clearance mean lower than men, which may increase their risk of falling.